Gambaran Inisiasi Menyusui Dini Di Rumah Sakit TK.II Pelamonia Makassar - Halimah, Nur (Indonesian Academia Health Sciences Journal, 2020)
Objective : Early breastfeeding initiationÂ  is a baby who starts breastfeeding himself immediately after birth given the chance of baby's skin contact with his mother's skin which is done for at least an hour immediately after birth, according to the World Health Organization (WHO) recommendations to reduce infant mortality and support exclusive breastfeeding , which is also the main cause of infant mortality in Indonesia is neonatal mortality by 46.2%.Methods : This type of research is descriptive analytic with cross sectional study design which is carried out in hospital. TK.II Pelamonia Makassar, the population in this study was puerperal mothers of 158 respondents.Results : The results of this study indicate that of the 158 respondents who did IMD as many as 69.6% and those who did not do IMD 30.4%. on the attitude variable obtained significant results (sig. = 0,000) or p value <0, 05 where there is a relationship between attitude and IMD.Conclusion : There is no meaningful relationship between knowledge and IMD at Tk Hospital. II Pelamonia Makassar and There is a significant relationship between attitude and IMD in Tk. II Pelamonia Makassar.